2018 12th International Conference on Research Challenges in Information Science (RCIS) 2018
DOI: 10.1109/rcis.2018.8406644
|View full text |Cite
|
Sign up to set email alerts
|

Where enterprise architecture development fails a multiple case study of governmental organizations

Abstract: Enterprise Architecture (EA) adoption by governmental organizations has been substantially increased not only to improve performance and efficiency, but as a prerequisite to E-Government implementation. Many efforts have been done to create frameworks and methodologies for government sector organizations to develop EA smoothly and flawlessly. Based on a survey in 2004, governmental organizations in Iran had been among the top ten countries in EA activities but since then it has faced with an ongoing decline. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
3
2
2

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 35 publications
0
5
0
Order By: Relevance
“…This study identified 17 EA development obstacles by investigating the process of EA development in 9 governmental organizations in Iran. Moreover, comparing the findings with the literature [23]- [32], [47], [54]- [61], this research reveals five obstacles that have been neglected in the previous studies: political issues of the government, change of management, outdated organizational statutes, lack of motivation among personnel, and EA conflict with governmental laws.…”
Section: Discussionmentioning
confidence: 75%
See 1 more Smart Citation
“…This study identified 17 EA development obstacles by investigating the process of EA development in 9 governmental organizations in Iran. Moreover, comparing the findings with the literature [23]- [32], [47], [54]- [61], this research reveals five obstacles that have been neglected in the previous studies: political issues of the government, change of management, outdated organizational statutes, lack of motivation among personnel, and EA conflict with governmental laws.…”
Section: Discussionmentioning
confidence: 75%
“…Many studies have discussed EA challenges in governmental organizations [11], [12], [23]- [32]. The aim of this study is first, to increase the understanding of EA development obstacles in governmental organizations and second, to look for a core category with the highest priority when addressing EA obstacles.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, we plan to perform a more systematic review to further prove our findings. Second, although we have grouped the majority of the reported challenges using TAM, there are still few challenges falling out of current model such as "old infrastructure [16] ". Further investigation on such challenges might be a useful complementation or enrichment to current model.…”
Section: Discussionmentioning
confidence: 99%
“…Concrete evidences regarding challenges of applying EA were presented. In each research, the word "challenge" or its synonyms such as "hindering factors" [15] or "obstacles" [16] were explicitly mentioned.…”
Section: Methodsmentioning
confidence: 99%
“…Enterprise Architecture (EA) development projects encounter different challenges, and not all of these projects end with success [26]. Challenges like the lack of establishing proper EA governance [13], lack of shared understanding [24], lack of leaders' trust [2], organizational politics [6], no management support [11], EA artifacts being outdated and of low quality [20], sabotaging the EA development by giving wrong information [21], and communication and collaboration challenges [3,6,13] have been identified. Thus, it is not surprising to see that 66 percent of EA projects did not fulfill the expectations of surveyed organizations [26].…”
Section: Introductionmentioning
confidence: 99%